The Effect of Demographic Variables on Teachers Decision to Quit or Stay on the Teaching Profession - Victor Mafone Alasa; Magdalene Ifeoma Ogbemudia (Gagasan Pendidikan Indonesia, 2021)
Demographic variables as predicate of public secondary school teachers' decision to quit or study in the teaching profession using Akwa Ibom, Nigeria as a case study was the central focus of this study. In this study two demographic variables were considered namely gender and academic qualification. The study utilized a sample size of 50 teachers randomly sampled from five public secondary schools and the ex-post-facto design. The data was collected using the “Demographic variable and Teachers” Decision to Quit or Stay in Teaching Profession Questionnaire (DVTDQSTPQ). The data was analyzed with an independent t-test and the result at 0.05 level of significance showed that gender and academic qualification had no significant influence on teachers' decision to quit or stay in the teaching profession.